"Aprovechamiento y conservación del mucílago de tres grupos genéticos de cacao (Theobroma cacao L.) para la obtención de miel, en la finca experimentales la represa" - Orejuela Hurtado, Fiama Pierina (2018)
The research was carried out in the Experimental Farm "La Represa" owned by the State Technical University of Quevedo, located in the Faita precinct, km 2.5 of the San Carlos parish, province of Los Ríos. Its geographic location 1 ° 03`18``of South latitude and 79 ° 25`24`` of West longitude, for the harvest, the extraction of the mucilage in the Canton Quevedo whose geographic location is 0 ° 13 '23 "south and 78 ° 30 '45 "west at a height of 74 meters above sea level. Whose objective was to obtain honey through the use and conservation of the mucilage of three genetic groups of cocoa (Theobroma cacao L.). A Completely Randomized Design (DCA) was applied, with 3 treatments and 6 repetitions, to determine differences between means the Tukey test (p≤ 0.05) was used. Variables studied: physical - chemical (pH, acidity, brix, humidity), productive (weight of almonds, weight of the shell, weight of the maguey, volume of the mucilage), sensory descriptors (taste, smell, color, taste, acceptability). The result referring to the number of ears (18.14) and weight of almonds (175.09) the T0 presented greater value, weight of the shell was obtained by T2 (399.58), for the weight of the maguey there were no statistically differences, volume of mucilage T1 (2.27). For pH the T1 (3.30) with the lowest value, for acidity, the highest value was presented in the T0 (17.21), coefficient of variation of 10.92%, humidity the lowest was obtained by the T0 treatment (55.51). In the sensory parameters, the CCN-51 shares attributes: honey odor, honey flavor, and dark brown color. Keywords: cocoa, mucilage extraction, honey, attributes.